Incidence of Acute Kidney Injury (AKI) after Endovascular Abdominal Aortic Aneurysm Repair (EVAR) and Impact on Outcome. Issue 5 (May 2015) - Saratzis, A.; Melas, N.; Mahmood, A.; Sarafidis, P.
<x xml:space="preserve">Abstract</x> Background Acute kidney injury (AKI) is an important post-operative complication that may impact on mortality, morbidity, and cost. The incidence after endovascular aneurysm repair (EVAR) remains unknown, as the current literature has not employed consistent definitions. The aim of this study is to assess the incidence of AKI after elective EVAR and examine the impact of AKI on mortality and cardiovascular morbidity using the current universally accepted definitions. Methods This was a cohort study using prospectively collected data, including consecutive patients undergoing elective EVAR for an infrarenal abdominal aortic aneurysm (AAA). Those with end stage renal failure were excluded. The primary endpoint was incidence of AKI as per the "Acute Kidney Injury Network" (AKIN), and "Kidney Disease Improving Global Outcomes" (KDIGO) criteria. Secondary endpoints included AKI stage, drop in estimated glomerular filtration rate (eGFR), and mortality and cardiovascular morbidity. Results 149 patients were included (16 females, 11%; mean age: 69 ± 8 years; mean AAA diameter: 6.0 ± 1.1 cm), 28 (18.8%) of whom developed AKI (26 patients classified as stage 1 and 2 as stage 2). Within 48 hours, those with AKI dropped their eGFR from 61 ± 20 mL/kg/1.73 m2 to 51 ± 20 units (p < .001), and those without from 75 ± 9 to 74 ± 10 units (p < .001). None required dialysis during a 33 ± 11 month follow up. Development of AKI was associated with mortality (HR 0.035, 95% CI: 0.005 to 0.240, p < .001) and cardiovascular morbidity (HR: 0.021, 95% CI: 0.004 to 0.11, p < .001) on adjusted regression analysis. Conclusions The incidence of AKI after EVAR is significant and is independently associated with medium-term mortality and morbidity.